A Survey of Various Scheduling Algorithms and types of Resources Provisioning in Cloud Environment (International Journal of Engineering and Computer Science, 2015)
Cloud computing is referring as simply “the cloud,” which is the delivery of on-demand computing resourceseverything from applications to data centers-over the Internet on a pay-for-use basis. In Cloud computing it contain four types of deployment model Private cloud, public cloud, hybrid cloud, community cloud. Cloud Services are Software as a Service (SaaS), Platform as a Service (PaaS) and Infrastructure as a Service (IaaS). As cloud charge you for what you use only, it is necessary to manage the resources. So, The managing of cloud resources and handling user’s request is important things for cloud computing. In this paper present various types of scheduling algorithms for resources managing and also define the resources provisioning techniques. Also define the comparison between scheduling Algorithm.